"Men don't cry": An Interpretative Phenomenological Analysis of Black South African Men's Experience of Divorce. Issue 2 (1st April 2019) - Muchena, Kudakwashe C.; Howcroft, Greg; Stroud, Louise A.
Abstract: The decision to divorce marks a turning point for every individual involved. It can be viewed as more than just a legal process. From a psychological perspective, it does not matter who initiated the divorce, since it always comes with emotional ramifications for all those involved. Statistically, there is a high rate of divorce in South Africa and there have been significant shifts in trends over time. While black South African men's experience of divorce has been relatively neglected in the research on divorce, it is important for understanding contemporary social arrangements and processes, and, in particular, for broadening the understanding of black South African men's lives. How black South African men describe their experience and respond to marital dissolution may point to their positions in the gender-structured community as well as illuminate how they interpret the nature of social practice, marriage, divorce and their position in society. The aim of the research reported on in this paper was to explore black South African men's experience of divorce. The theoretical framework underpinning this qualitative study was broadly that of Symbolic Interactionism, with Interpretative Phenomenological Analysis (IPA) employed as both the research design and data analytic theory and process. The eight participants were volunteers who were recruited purposively. In keeping with IPA guidelines, data-collection proceeded by means of biographical questionnaires and semi-structured interviews. The emerging themes were grouped into three superordinate themes, namely, perceptions of divorce, social support, and experiencing of pain. Each superordinate theme had corresponding subordinate themes and experiential claims. Weed's (2008) recommendations for the interpretative synthesis of interview data were applied.